2009
DOI: 10.1007/s00221-009-2014-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of error-amplification and haptic-guidance training techniques for learning of a timing-based motor task by healthy individuals

Abstract: Performance errors drive motor learning for many tasks. Some researchers have suggested that reducing performance errors with haptic guidance can benefit learning by demonstrating correct movements, while others have suggested that artificially increasing errors will force faster and more complete learning. This study compared the effect of these two techniques--haptic guidance and error amplification--as healthy subjects learned to play a computerized pinball-like game. The game required learning to press a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
114
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(140 citation statements)
references
References 48 publications
(66 reference statements)
22
114
3
1
Order By: Relevance
“…In their study, Milot et al (2010) found that training with the haptic guidance technique significantly reduced errors with regard to pressing the button to activate the virtual flipper on time. In comparison to the error amplification technique, they found that haptic guidance was more beneficial for a subset of less-skilled players.…”
Section: Technique #1: Haptic Guidancementioning
confidence: 99%
See 2 more Smart Citations
“…In their study, Milot et al (2010) found that training with the haptic guidance technique significantly reduced errors with regard to pressing the button to activate the virtual flipper on time. In comparison to the error amplification technique, they found that haptic guidance was more beneficial for a subset of less-skilled players.…”
Section: Technique #1: Haptic Guidancementioning
confidence: 99%
“…case study #3: Pinball game simulator Milot et al (2010) developed a pinball game simulator to investigate the effects of haptic guidance and error amplification on training motor skills. The concept of haptic guidance is to use force feedback to guide the user's movements in order to demonstrate a desired movement trajectory to the motor system for later imitation.…”
Section: Technique #3: Automated Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the practice of adaptive haptic guidance, or the use of haptic signals to navigate a user through a motion task based on the user's skill level, has been suggested as a more scalable approach, so long as it is delivered on an as-needed basis [62]. It can be demonstrated that this implementation of haptic feedback does not lose effectiveness if the complexity of the signal matches the complexity of the motion task [63]. One example of such guidance is a haptic tunnel in which a user's motion can be considered correct in the 3D spatial domain [64].…”
Section: Hapticsmentioning
confidence: 99%
“…Since nondisabled subjects can already perform all the commonly used movements targeted for functional training in patients with stroke, studies focus on learning a difficult or novel task when assisted by the robot. This approach has led to insights into the role of haptic guidance in motor learning, which may have implications for stroke recovery [68][69][70].…”
Section: Introductionmentioning
confidence: 99%